1997
DOI: 10.1038/sj.sc.3100359
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic hyperreflexia associated with recurrent cardiac arrest: Case Report

Abstract: Autonomic hyperre¯exia is a condition which may occur in individuals with spinal cord injuries above the splanchnic sympathetic out¯ow. Noxious stimuli can produce profound alterations in sympathetic pilomotor, sudomotor, and vasomotor activity, as well as disturbances in cardiac rhythm. A case of autonomic hyperre¯exia in a patient with C6 tetraplegia with recurrent ventricular ®brillation and cardiac arrest illustrates the profound e ects of massive paroxysmal sympathetic activity associated with this condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
1
14
1
1
Order By: Relevance
“…Importantly, these molecular changes were associated with an increase in the intrinsic excitability and conductive properties of the heart as well as a reduced electrical stimulation threshold to induce ventricular arrhythmias. These results are consistent with clinical reports that suggest an increased susceptibility to cardiac arrhythmias (4,11,15) as well as alterations in the electrocardiograms of individuals with spinal cord injuries (27,33). Furthermore, these results extend a recent report that documents a lower electrical stimulation threshold to induce ventricular arrhythmias in hypertensive paraplegic rats (42).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Importantly, these molecular changes were associated with an increase in the intrinsic excitability and conductive properties of the heart as well as a reduced electrical stimulation threshold to induce ventricular arrhythmias. These results are consistent with clinical reports that suggest an increased susceptibility to cardiac arrhythmias (4,11,15) as well as alterations in the electrocardiograms of individuals with spinal cord injuries (27,33). Furthermore, these results extend a recent report that documents a lower electrical stimulation threshold to induce ventricular arrhythmias in hypertensive paraplegic rats (42).…”
Section: Discussionsupporting
confidence: 82%
“…Many case reports document cardiac arrhythmias in individuals with spinal cord injury (4,11,15). Spinal cord injury may increase the susceptibility to ventricular arrhythmias by altering cardiac autonomic control.…”
mentioning
confidence: 99%
“…Cardiac arrest from ventricular fibrillation has been described. 4 Retinal haemorrhage, subarachnoid haemorrhage and intracranial haemorrhage 5 have also been reported.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the threshold of 180 mmHg is in contrast to literature that has shown less severe AD (i.e., SBP \180 mmHg) to be implicated in life-threatening events and death in individuals with SCI [10]. A clinical review of 32 cases in the published literature by Wan and Krassioukov [10] found that episodes of AD during which SBP is \180 mmHg (the point at which the IPC considers AD to be 'hazardous') has been associated with cerebral hemorrhage [25,29], seizure [27], cardiac arrhythmia [64,65] and arrest [28], and pulmonary edema [66,67] in individuals with SCI. Among the 32 cases reviewed, the mean SBP during life-threatening cases and cases that resulted in death was found to be 181 ± 35 and 214 ± 41 mmHg, respectively.…”
Section: Rationale For the Current Approach To Testing For Boostingmentioning
confidence: 99%
“…It should be noted that individuals with cervical SCI usually have lower resting arterial BP than that typically encountered in individuals with lower injuries [24]; thus, a relatively 'normal' BP may still be representative of AD. If an episode of AD goes undiagnosed or left untreated, this may lead to severe complications such as cerebral hemorrhage [25], myocardial ischemia [26], seizures [27] and arrhythmias [28], or death [10,29]. Episodes of AD may be accompanied by brady-or tachycardia, excessive sweating, piloerection, anxiety, blurred vision, and/or headache [11].…”
Section: Autonomic Dysreflexiamentioning
confidence: 99%